Analisis Beban Pencemar dan Kapasitas Asimilasi di Estuari Sungai Belau Teluk Lampung - Sembel, Luky (Maspari Journal : Marine Science Research, 2012)
ABSTRACTUtilization around of Belau Rivers was diverse, such as agriculture, industry, households, hotels, markets, residential population and fishing boats. According to the explanation, the purpose of this study was to determine distribution and concentration distribution patterns of Pb, Cd, and Cr which evaluated from the distribution of salinity, calculate the assimilation capacity in marine and analyzing the direction of environmental management Estuary Belau at Lampung Bay. The data was analyzed by using the view pattern of relationship between dissolved heavy metals and salinity through mixing graph approach. Furthermore, to know the pollutant load and capacity of assimilation were use a graph of the relationship between the concentration of each parameter with pollutant load on these parameters. The results analysis of pollutant loads and assimilation capacity showed that the parameters of TSS, BOD and COD were still able to perform self purification, whereas for the parameters of nitrate, phosphate, Pb, Cd and Cr were unable to perform self-purification. The management must be built not only within the autority of Lampung Government and the staffs, but also must be holistic upstream to downstream along the river that involves several government autority. Keywords: Pollution Load , heavy metals, the assimilation capacity, Estuary Belau